(untitled) (Universal International Scientific Journal, 2026)
A practical solution to the challenge of simple and stable blue LEDs is proposed: a solution-processed single-layer device based on a perovskite–polymer composite. Stable blue electroluminescence at low operating voltages is demonstrated, and prospects for further optimization and practical implementation are outlined.